Clinicoradiological Profile of Patients Presenting With Idiopathic Intracranial Hypertension in Outpatient Department of Neurology, Jinnah Postgraduate Medical Centre - Nisha, .; Sher, Khalid; Muhammad, Fatima Ghulam; Devi, Lata; Ahmad, Rizwana Malahat; Farooq, Maheen (Biological and Clinical Sciences Research Journal, 2025)
Idiopathic intracranial hypertension (IIH), a disorder characterized by elevated intracranial pressure without an identifiable cause, presents with varied clinical and radiological features. Early recognition and characterization are essential to prevent complications such as vision loss. Data from Pakistan regarding the clinicoradiological spectrum of IIH remains limited. Objective: To determine the clinicoradiological profile of patients presenting with idiopathic intracranial hypertension in the outpatient department of neurology at Jinnah Postgraduate Medical Centre (JPMC), Karachi. Methods: This descriptive cross-sectional study was conducted at Ward 28, Department of Neurology, JPMC, Karachi, from January 10, 2025, to April 10, 2025, following approval from the institutional ethical review board. A total of 90 patients aged 18–50 years of both genders with a confirmed diagnosis of IIH were enrolled using non-probability consecutive sampling. Clinical features including headache, pulsatile tinnitus, visual symptoms, and retrobulbar pain were documented. Radiological assessments using MRI and MRV focused on identifying features such as empty sella, tortuous optic nerves, transverse sinus stenosis, and scleral flattening. Data were analyzed using SPSS Version 25. Results: The mean age of patients was 35.02 ± 9.8 years. Females constituted a greater proportion (57%, n=51) compared to males (43%, n=39). Most common clinical symptoms were blurred vision (59%, n=53), transient visual obscuration (TVO) (57%, n=51), retrobulbar pain (56%, n=50), and headache (53%, n=48). Radiological findings showed empty sella in 42% (n=38), tortuous optic nerves in 44% (n=40), transverse sinus stenosis in 49% (n=44), and scleral flattening in 51% (n=46). Conclusion: This study underscores the predominance of IIH in middle-aged females and highlights visual disturbances and retrobulbar pain as frequent presenting complaints. Radiological findings such as transverse sinus stenosis and scleral flattening were prevalent, supporting their utility in the diagnostic evaluation of IIH. A multidisciplinary approach is crucial for early diagnosis and vision preservation.